Membrane-processed honey samples for pollen characterization with health benefits. (April 2023) - Nabila; Ahmad, Mushtaq; Althobaiti, Ashwaq T.; Ali, Wahid; Masood, Khansa; Ramadan, Mohamed Fawzy; Chaudhary, Bisha; Zafar, Muhammad; Akhtar, Muhammad Saeed; Sultana, Shazia; Zahmatkesh, Sasan; Mehmood, Tariq; et al.
Abstract: Better processing techniques must be utilized widely due to the rising demand for honey. The most common honey processing techniques are applied to melissopalynomorphs to check the quality and quantity of valuable honey using microporous ultrafiltration membranes. It is essential to have the ability to selectively filter out sugars from honey using ultrafiltration. This study authenticated 24 honey samples using membrane reactors ultrafiltration protocol to describe the pollen spectrum of dominant vegetation. The purpose of this study was also to explore nutritional benefits as well as the active phytochemical constituents of honey samples. Honey samples were collected and labeled Acacia, Eucalyptus, and Ziziphus species based on plant resources provided by local beekeepers. A variety of honeybee flora was collected around the apiaries between 2020 and 2021. Honey analysis revealed that the pollen extraction of 24 bee foraging species belonging to 14 families. The honey membrane technology verified the identities of honey and nectar sources. Also, pollen identified using honey ultrafiltration membranes revealed dominant resources: Acacia spp. (69%), Eucalyptus spp. (52%) and Ziziphus spp. Honey filtration using a membrane technology classified 14 samples as unifloral, represented by six dominant pollen types. The absolute pollen count in the honey sample revealed that 58.33% (n = 14) belong to Maurizio's class I. Scanning ultrasculpturing showed diverse exine patterns: reticulate, psilate, scabrate-verrucate, scabrate-gemmate, granulate, perforate, microechinate, microreticulate, and regulate to fossulate for correct identification of honey pollen types. Honey ultrafiltration should be utilized to validate the botanical sources of honey and trace their biogeographic authenticity. Thus, it is imperative to look at the alternative useful method to identify the botanical origin of filtered honey. It is critical to separate honey from adulteration by a standardized protocol. Membrane technology has yielded significant outcomes in the purification of honey. Graphical abstract: Image 1 Highlights: Honey membrane reactor ultrafiltration was employed. Honey analysis revealed a diverse pollen spectrum. Membrane reactors are needed for honey processing. SEM Characterization of Honey pollen types.